Analgesic action of Rubimaillin in vitro and in vivo - Yan, Wanli; Jiang, Zhonglei; Fan, Fengyun (Cellular and Molecular Biology, 2020)
Pain, a common symptom in clinics, is a serious impediment to quality of life. The analgesic drugs presently in use have poor efficacy, and are associated with undesirable side effects. Rubimaillin (Rub) is a naphthoquinone compound extracted from Chinese herbal medicine, and it has various biological activities. In this study, the analgesic effect of Rub, and its mechanism of action were investigated using glacial acetic acid-induced mice writhing model and a mice model of neurogenic and inflammatory bipolar pain. Analgesic effects were measured in different experimental groups. In vitro, RAW 264.7 cells were used to investigate the release of nitric oxide (NO), iNOS and COX-2 protein in RAW 264.7 cells stimulated with lipopolysaccharide (LPS). The results revealed that Rub reduced the number of acetic acid-induced writhing in mice, inhibited formalin-induced biphasic pain response, and suppressed the production of NO in RAW 264.7 cells. The mechanisms involved in the analgesic and anti-inflammatory effects of rub may be related to the inhibition of cyclooxygenase-2 (COX-2), endogenous inflammatory mediators, and reduction in the content of pain-induced mediators.